Pengaruh Psikoedukasi “Kenali Emosimu, Atur Hatimu!” terhadap Pemahaman Regulasi Emosi Pada Siswa Sekolah Dasar - Jafar, Eka Sufartianinsih (AIJER: Algazali International Journal Of Educational Research, 2025)
This study aims to examine the effectiveness of visual psychoeducation themed “Know Your Emotions, Manage Your Heart!” in improving fourth-grade students' understanding of emotional regulation at SD X. This study used a quasi-experimental method with a one-group pre-test and post-test design. A total of 36 fourth-grade students participated in the program. The intervention was conducted through poster presentations and a simple question-and-answer session. Normality test results showed that the data were normally distributed, and paired sample t-test analysis revealed a significant difference between pre-test and post-tests cores with a significance value of p = 0.039 (p < 0.05). The mean post-test score was higher than the pre-test score, indicating an improvement in students' understanding of emotional regulation after participating in the psychoeducation. Thus, visual psychoeducation using posters is effective in increasing emotional awareness and supporting mental health education efforts in elementary schools.